2014
DOI: 10.1002/hed.23823
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of the modified Glasgow prognostic score in patients with advanced head and neck cancer

Abstract: Our results suggest that the mGPS is useful for predicting outcome in patients with advanced head and neck cancer and should be included in their routine clinical assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 34 publications
4
55
0
Order By: Relevance
“…[1519] Published data also show that elevated CRP values and neutrophil to lymphocyte ratios have adverse effects on the survival of patients with localized head and neck cancer, treated with curative intent. [2530] The calculated cutoff values for leukocytes and CRP in this study were 9.25 G/L and 8.5 mg/L respectively, which is close to the upper normal limits. High CRP and high leukocytes, which may reflect inflammation caused by the tumor as well as individual comorbidities, were also poor prognostic factors for patients in this cohort.…”
Section: Discussionsupporting
confidence: 73%
“…[1519] Published data also show that elevated CRP values and neutrophil to lymphocyte ratios have adverse effects on the survival of patients with localized head and neck cancer, treated with curative intent. [2530] The calculated cutoff values for leukocytes and CRP in this study were 9.25 G/L and 8.5 mg/L respectively, which is close to the upper normal limits. High CRP and high leukocytes, which may reflect inflammation caused by the tumor as well as individual comorbidities, were also poor prognostic factors for patients in this cohort.…”
Section: Discussionsupporting
confidence: 73%
“…Cancer cachexia is caused by activated cytokines and is commonly found in patients with cancer . Several studies have identified the Glasgow prognostic score as a significant prognostic score for many tumor types, including head and neck cancers . Our study also demonstrated that a higher pretreatment Glasgow prognostic score can be correlated with advanced tumor stage and that the Glasgow prognostic score is also an independent prognostic parameter.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, our findings also demonstrated that a higher pretreatment GPS was associated with poor disease-free survival (DFS) and OS, which is in accordance with a previous study reported by Nakayama et al . (8). Since the GPS can reflect the degree of cachexia and malnutrition (6), and considering that the post-CCRT GPS declined in most patients in our study, we further analyzed the prognostic role of post-CCRT GPS as a biomarker for the follow-up of the patients’ nutritional status and found that the post-CCRT GPS level was an independent prognostic factor in the multivariate analysis, rather than the pre-CCRT GPS ( Table 2 ), implying that poor nutrition after CCRT can predict survival.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is reasonable to use the GPS as a biomarker for malnutrition surveillance. Further, the pretreatment GPS has been shown to be a prognostic factor in head and neck cancer (8), with the overall survival (OS) and recurrence-free survival (RFS) being higher when the GPS was low. …”
Section: Introductionmentioning
confidence: 99%